The work of the Topographic Commission in La Paz, Bolivia, in the mid-19th century and the construction of the national State - Machaca, Victor Hugo (2023)
This article shows the work of the members of the Topographic Commission in La Paz, Bolivia, in order to understand the consolidation of the national State through cartography in the mid-nineteenth century. The city of La Paz was the center of its activities for the elaboration of an urban plan, a topographic map of the department and another of Lake Titicaca, which are analyzed in the context of the elaboration of a national geographical map. To develop this research, information from archives and libraries of different Bolivian cities and the National Historical Archive of Spain has been consulted.